Arrhythmogenic Calmodulin Mutations Disrupt Intracellular Cardiomyocyte Ca2+ Regulation by Distinct Mechanisms. Issue 3 (23rd June 2014) - Yin, Guo; Hassan, Faisal; Haroun, Ayman R.; Murphy, Lisa L.; Crotti, Lia; Schwartz, Peter J.; George, Alfred L.; Satin, Jonathan
Abstract : Background: Calmodulin (CaM) mutations have been identified recently in subjects with congenital long QT syndrome (LQTS) or catecholaminergic polymorphic ventricular tachycardia (CPVT), but the mechanisms responsible for these divergent arrhythmia‐susceptibility syndromes in this context are unknown. We tested the hypothesis that LQTS‐associated CaM mutants disrupt Ca 2+ homeostasis in developing cardiomyocytes possibly by affecting either late Na current or Ca 2+ ‐dependent inactivation of L‐type Ca 2+ current. Methods and Results: We coexpressed CaM mutants with the human cardiac Na channel (NaV 1.5) in tsA201 cells, and we used mammalian fetal ventricular cardiomyocytes to investigate LQTS‐ and CPVT‐associated CaM mutations (LQTS‐ and CPVT‐CaM). LQTS‐CaM mutants do not consistently affect L‐type Na current in heterologous cells or native cardiomyocytes, suggesting that the Na channel does not contribute to LQTS pathogenesis in the context of CaM mutations. LQTS‐CaM mutants (D96V, D130G, F142L) impaired Ca 2+ ‐dependent inactivation, whereas the CPVT‐CaM mutant N54I had no effect on Ca 2+ ‐dependent inactivation. LQTS‐CaM mutants led to loss of Ca 2+ ‐transient entrainment with the rank order from greatest to least effect: CaM‐D130G CaM‐D96V>>CaM‐F142L. This rank order follows measured Ca 2+ ‐CaM affinities for wild‐type and mutant CaM. Acute isoproterenol restored entrainment for CaM‐130G and CaM‐D96V but caused irreversible cytosolic Ca 2+ overload for cells expressing a CPVT‐CaM mutant. Conclusions: CaM mutations associated with LQTS may not affect L‐type Na + current but may evoke defective Ca 2+ ‐dependent inactivation of L‐type Ca 2+ current.